Creatine supplementation and renal function - myths and evidence - a narrative review - Grzyb, Izabela; Szewczyk, Jan; Smolińska, Alicja; Bołoz, Maria; Haba, Sylwia; Dapkiewicz, Ewa; Gąsowski, Dawid (Journal of Education, Health and Sport, 2026)
Background: Creatine is one of the most commonly used ergogenic supplements. However, many myths and misconceptions about creatine supplementation regarding renal function are still popular even among medical professionals. Aim: The aim of this study was to summarise the current knowledge regarding creatine supplementation and renal function, as well as to evaluate the most common myths associated with its use and to discuss creatine supplementation in patients with chronic kidney disease. Particular attention was paid to the five most common myths. Methods and materials: A review of the literature in Polish and English was conducted using the PubMed/MEDLINE and Google Scholar databases for the period from 1998 to March 2026. A total of 189 publications were analysed. Results: Current scientific evidence suggests that creatine supplementation does not cause kidney damage in healthy individuals when administering doses within recommended range. An increase in serum creatinine levels in individuals supplementing creatine does not necessarily indicate impaired kidney function, as it may result from increased creatine intake and its metabolic processes, rather than actual organ damage. Assessment of kidney function in individuals using creatine should not be based solely on serum creatinine levels; other indicators should also be considered. It has not been confirmed that creatine supplementation increases the risk of kidney stones or leads to permanent disturbances in water balance. Available studies indicate that long-term use of creatine is well tolerated and safe; however, high-quality studies covering diverse populations and long follow-up periods are still needed. Conclusions: Current scientific evidence does not support the notion that creatine supplementation, when used at recommended doses, causes renal dysfunction in healthy individuals. However, careful interpretation of renal markers and further studies in clinical populations are necessary.